Human Paraoxonase-2 (PON2): Protein Functions and Modulation - Giuseppe Manco; Elena Porzio; Teresa Maria Carusone (MDPI AG, 2021)
PON1, PON2, and PON3 belong to a family of lactone hydrolyzing enzymes endowed with various substrate specificities. Among PONs, PON2 shows the highest hydrolytic activity toward many acyl-homoserine lactones (acyl-HL) involved in bacterial quorum-sensing signaling. Accordingly, defense against pathogens, such as Brevundimonas aeruginosa (B. aeruginosa), was postulated to be the principal function of PON2. However, recent findings have highlighted the importance of PON2 in oxidative stress control, inhibition of apoptosis, and the progression of various types of malignancies. This review focuses on all of these aspects of PON2.